Daya terima dan kandungan gizi dimsum berbasis hati ayam, daun kelor, dan jamur tiram sebagai camilan untuk remaja putri - Wardhani, Selsabilla Aulia; Palupi, Fitria Dhenok; Hadisuyitno, Juin (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Prevention of anemia can be done by consuming foods that are sources of iron. One source of animal food that contains heme iron and has a higher biovalidity value than other sources of iron is chicken liver.  One vegetable that has a high iron content is Moringa (Moringa oleifera). White oyster mushrooms are low in fat but high in protein.Objectives: The study aims to analyze the nutritional quality and organoleptic quality of dimsum formulations of chicken liver, moringa leaves and oyster mushrooms as snacks for anemic teenage girls.Methods: This research uses an experimental research type with a completely randomized design (CRD). The research was conducted at the Food Technology Science Laboratory (ITP) of the Malang Health Polytechnic Nutrition Department on June 2024. Organoleptic quality testing was carried out using a hedonic test using 25 semi-trained panelists. Determination of the best treatment level using the effectiveness index method. Statistical tests used the Kruskal Wallis test and the Mann Whitney advanced test.Results: Shows that the dimsum formulation of chicken liver, oyster mushrooms and Moringa leaves meets the nutritional requirements of adolescent girls aged 13-15 years with a snack percentage of 10% (empirically). There were significant differences in the organoleptic quality parameters of taste (p=0,030) and texture (p=0,036), while color (p=0,076) and texture (p=0,319) showed no significant differences. At the best treatment level, namely P1, it can meet the energy and nutritional needs of adolescent girls.Conclusion: The formulation of chicken liver, oyster mushroom and moringa leaf dimsum shows significant differences in organoleptics taste and texture.